A study of the story of the Prophet Yusuf in the Qur'an with a psychological approach - Saufa, Syifa Nur (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the story of the Prophet Yusuf in Surah Yusuf using a psychological approach to understand the spiritual values contained in the story. The method used is a qualitative study with a psychological Quranic interpretation approach through a review of related verses and interpretations from Tafsir Al-Azhar (Buya Hamka) and Tafsir Al-Misbah (Quraish Shihab). The results of the study indicate that the story of the Prophet Yusuf contains important psychological themes such as resilience to trauma, self-control, forgiveness, and spirituality as a foundation for psychic strength. This story not only provides motivation but also psychological solutions in dealing with conflict, social pressure, and life's temptations. In conclusion, the integration of spiritual and psychological values in Surah Yusuf can be used as a reference in the development of spirituality-based therapy and the formation of a resilient and noble Islamic personality. This study has practical implications for Islamic psychology and religious education in the Indonesian socio-cultural context.